Mitigation of soil salinity by biochar and halophytes - Qiang Xu; Yibin Xu; Hanji Xia; Han Han; Mingsi Li; Ping Gong; Chunxia Wang; Yufang Li; Pengfei Li; Hongguang Liu (Geoderma)
Biochar is widely recognized as a significant agricultural management practice globally. Nevertheless, its application typically emphasizes incorporation into topsoil, while the potential benefits of biochar interlayers in ameliorating saline wastelands in arid regions remain insufficiently understood. A study was conducted to investigate the impact of biochar interlayers on the dynamics and distribution of water and salt in saline wasteland soils cultivated with Suaeda salsa (S. salsa) during growth and non-growth periods. Over three consecutive years, a field experiment was implemented with four biochar application rates: 0 Mg/ha (CK), 15 Mg/ha (M1), 45 Mg/ha (M2), and 75 Mg/ha (M3). The biochar was uniformly distributed at a depth of 40 cm, and the original soil from the 0–40 cm layer was refilled. The results demonstrate that biochar interlayers reduced groundwater evaporation and minimized surface salt accumulation during the non-growth period, leading to a reduction in soil salinity by 13.14 %–49.62 % in the 0–40 cm layer, with a bimodal salinity distribution pattern observed at 0 cm and 45 cm depths. During the growth period, biochar significantly enhanced water retention and reduced salinity. Water content increased by 0.14 %–18.92 %, and salt content decreased by 24.51 %–36.64 % within the 0–40 cm soil layer, with salt aggregating at 40–60 cm depths. The root system of S. salsa utilized water and salt from the biochar interlayer, resulting in a marked increase in salt content within plant organs. Concentrations of Na+, Cl−, and SO42− decreased, while K+, Ca2+, and Mg2+ levels increased in these organs. The yield of S. salsa improved by 22.12 %–65.92 %, and salt absorption efficiency rose by 30.62 %–85.03 %. However, excessive biochar applications may hinder surface soil desalination and pose risks of secondary salinization. Thus, a moderate biochar application rate of 45 Mg/ha is recommended for effective water retention and salt suppression in saline wastelands.